2019
DOI: 10.1088/2050-6120/ab47f2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH and ionic strength on the fluorescence properties of a red emissive DNA-stabilized silver nanocluster

Abstract: DNA-stabilized silver nanoclusters (DNA-AgNCs) are a class of promising fluorophores for imaging and sensing applications. All aspects of their spectroscopic properties are not yet fully characterized, leaving this field still with a number of fundamental studies to be addressed. In this work, we studied the spectroscopic properties of red-emitting DNA-AgNCs at different pH (5 to 9) and ionic strength μ (0.005 to 0.5). The photophysical properties of high performance liquid chromatography (HPLC) purified DNA-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…27 Other studies, however, have not observed this decrease in long cytosine-rich sequences. 61 By using a DNA sequence similar to the ones used in this work, Shah et al…”
Section: Discussionmentioning
confidence: 99%
“…27 Other studies, however, have not observed this decrease in long cytosine-rich sequences. 61 By using a DNA sequence similar to the ones used in this work, Shah et al…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis and purification of DNA-AgNCs DNA-templated silver nanoclusters (DNA-AgNCs) were synthesized as described elsewhere. [29,30] Briefly, ss-DNA (5'-TTCCCACC-CACCCCGGCCC-3', IDT) dissolved in nuclease-free water (IDT) and AgNO 3 (> 99.998 %, Fluka Analytical) were mixed (1 : 10 ratio) in a 10 mM ammonium acetate (NH 4 OAc) solution. After 10 minutes at room temperature, NaBH 4 was added ([NaBH 4 ] : [AgNO 3 ] = 1 : 2) and the resulting sample was stored overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The emissive state of the DNA-AgNCs has an average decay time of 2.5 ns when probed at 640 nm and 25°C, while the sample displays a limiting anisotropy value of 0.4 and a rotational correlation time of 2.6 ns at 25°C (Table 1). [29,30] Rotational correlation times [31,32] measured at different temper-atures (10, 25, 37 and 45°C) were used to calculate the hydrodynamic volume of the DNA-AgNCs, yielding a value of about 12 nm 3 . Based on this value and the arrangement proposed for other types of DNA-AgNCs, [1,33] it can be assumed that the DNA-AgNCs comprise a single oligonucleotide strand surrounding a metal core of about 10 to 30 Ag atoms.…”
Section: Dna-agncs Spectroscopic Characterizationmentioning
confidence: 99%
See 2 more Smart Citations